Diversity and origin of carotenoid biosynthesis: its history of coevolution towards plant photosynthesis. Issue 2 (19th August 2021) - Sandmann, Gerhard
Summary: The development of photosynthesis was a highlight in the progression of bacteria. In addition to the photosystems with their structural proteins, the photosynthesis apparatus consists of different cofactors including essential carotenoids. Thus, the evolution of the carotenoid pathways in relation to the functionality of the resulting structures in photosynthesis is the focus of this review. Analysis of carotenoid pathway genes indicates early evolutionary roots in prokaryotes. The pathway complexity leading to a multitude of structures is a result of gene acquisition, including their functional modifications, emergence of novel genes and gene exchange between species. Along with the progression of photosynthesis, carotenoid pathways coevolved with photosynthesis according to their advancing functionality. Cyanobacteria, with their oxygenic photosynthesis, became a landmark for evolutionary events including carotenogenesis. Concurrent with endosymbiosis, the cyanobacterial carotenoid pathways were inherited into algal plastids. In the lineage leading to Chlorophyta and plants, carotenoids evolved to their prominent role in protection and regulation of light energy input as constituents of a highly efficient light‐harvesting complex.